The 'Consensus Genvensis' revisited: the Genesis of the Genevan consensus of divine election in 1551 - E. A. de Boer (Acta Theologica)
In the weekly Bible study meetings on Fridays in Geneva, called les congrégations, biblical books were expounded in lectio continua. On one occasion the doctrine of divine election was presented over against the intervention of Jerome Bolsec. The ministers of Geneva presented their internal consensus on predestination and sought the approval of the Swiss churches. This paper argues on historical, literary and material grounds that not Calvin’s book De aeterna praedestinatione Dei of early 1552, but the Congrégation sur l’élection éternelle de Dieu of 18 December 1551, should be identified as the ‘Consensus Genevensis’. The doctrine of predestination was not a particularity of John Calvin’s, but a point of teaching the Scriptures, shared by the Genevan ministers.